2006
DOI: 10.1002/cav.124
|View full text |Cite
|
Sign up to set email alerts
|

Understanding visuo‐motor primitives for motion synthesis and analysis

Abstract: The problem addressed in this paper concerns the representation of human movement in terms of atomic visuo-motor primitives considering both generation and perception of movement. We introduce the concept of kinetology, the phonology of human movement, and five principles on which such a system should be based: compactness, view-invariance, reproducibility, selectivity, and reconstructivity. We propose visuo-motor primitives and demonstrate their kinetological properties. Further evaluation is accomplished wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Some kinematic features are joint positions relative to other points or planes [Jenkins and Matarić 2003;Jenkins and Matarić 2004;Müller et al 2005;Peng 2010;Reng et al 2006], linear or angular velocity [Bernhardt and Robinson 2007;Fod et al 2002;Ilg et al 2004;Kwon and Shin 2005;Mezger et al 2005;Mori and Uehara 2001;Osaki et al 2000;Shiratori et al 2003], linear or angular acceleration [Bindiganavale and Badler 1998;Guerra-Filho and Aloimonos 2006], and curvature [Zhao and Badler 2005;Wang et al 2001]. Some changes in these kinematic features that are used to determine segment boundaries are local minima or maxima, zero-crossings, and thresholds.…”
Section: Related Workmentioning
confidence: 99%
“…Some kinematic features are joint positions relative to other points or planes [Jenkins and Matarić 2003;Jenkins and Matarić 2004;Müller et al 2005;Peng 2010;Reng et al 2006], linear or angular velocity [Bernhardt and Robinson 2007;Fod et al 2002;Ilg et al 2004;Kwon and Shin 2005;Mezger et al 2005;Mori and Uehara 2001;Osaki et al 2000;Shiratori et al 2003], linear or angular acceleration [Bindiganavale and Badler 1998;Guerra-Filho and Aloimonos 2006], and curvature [Zhao and Badler 2005;Wang et al 2001]. Some changes in these kinematic features that are used to determine segment boundaries are local minima or maxima, zero-crossings, and thresholds.…”
Section: Related Workmentioning
confidence: 99%
“…Rui and Anandan [23] used principal components of frame-toframe optical-flow to discover temporal trajectories of human motion in video. Recently, Guerra-Filho and Aloimonos [9], [10] presented a linguistic framework for modeling and learning of human activity representations. The low level representation of their framework, motion primitives, referred to as kinetemes, are studied as the foundation for a kinetic language.…”
Section: Previous Workmentioning
confidence: 99%
“…Research that addresses the problem of detection, recognition and synthesis of human human motion have gained substantial interests from both academia and industry over the last few years due to the large number of applications [1], [20], [13], [15], [22]. Unsupervised techniques for learning motion primitives from data have recently drawn the interest of many scientists in computer vision [9], [28], [27], [17] and computer graphics [4], [16], [3], [8]. Although previous research has shown promising results, recognizing human activities and factorizing human motion into primitives and actions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the detection, recognition, or synthesis in these applications greatly depends on the spatial and temporal resolution of motion databases, as well as the complexity of the models. Unsupervised techniques to learn motion primitives from training data have recently attracted the interest of many scientists in computer vision [4], [5], [6], [7], [8], [9], [10], [11], [12] and computer graphics [13], [14], [15], [16], [17], [18], [19], [20]. Fig.…”
mentioning
confidence: 99%
“…Over the last few years, several approaches for unsupervised segmentation of activities have been proposed (see, for example, [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18]). HACA presents several advantages:…”
mentioning
confidence: 99%